2015
DOI: 10.1016/j.bbamcr.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The stromal cell-surface protease fibroblast activation protein-α localizes to lipid rafts and is recruited to invadopodia

Abstract: Fibroblast activation protein alpha (FAPα) is a cell surface protease expressed by cancer-associated fibroblasts in the microenvironment of most solid tumors. As there is increasing evidence for proteases having non-catalytic functions, we determined the FAPα interactome in cancer-associated fibroblasts using the quantitative immunoprecipitation combined with knockdown (QUICK) method. Complex formation with adenosin deaminase, erlin-2, stomatin, prohibitin, Thy-1 membrane glycoprotein, and caveolin-1 was furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 63 publications
(77 reference statements)
0
18
0
Order By: Relevance
“…26 Yang et al 14 inhibited FAP with Talabostat does not reduce levels of its downstream CCL-2 secretion. Knopf et al 25 suggested that FAP directly binds to erlin-2, stomatin, and caveolin-1. However, it is not clear whether this binding is due to FAP enzyme activity pattern or nonenzyme activity pattern.…”
Section: Discussionmentioning
confidence: 99%
“…26 Yang et al 14 inhibited FAP with Talabostat does not reduce levels of its downstream CCL-2 secretion. Knopf et al 25 suggested that FAP directly binds to erlin-2, stomatin, and caveolin-1. However, it is not clear whether this binding is due to FAP enzyme activity pattern or nonenzyme activity pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Peptides were eluted in a linear gradient with increasing concentration of 5 mM KH 2 PO 1 M KCl 25% acetonitrile pH 2.7; 10 -14 fractions were collected and desalted using self-packed C18 STAGE tips (Empore; 3 M, St Paul, MN) (34). Differential proteomics samples were pre-fractionated by SDS-PAGE as described previously (31). For nanoflow-LC-MS/MS analysis, samples for quantitative proteomic comparison were analyzed on a Qstar Elite (AB Sciex, Framingham, MA) and TAILS samples on an Orbitrap XL (Thermo Scientific GmbH, Bremen, Germany) mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Some PHB1 proteins have been reported to interact with low density detergent-insoluble lipid raft domains in the plasma membrane 26 , 51 , acting as transmembrane adapters to activate downstream signals 14 , 52 , 53 . Previous studies also identified that PHB1 on plasma membrane acts as a viral receptor protein to facilitate virus entry into host cells 8 , 54 , 55 .…”
Section: Location and Function Of Phb1 And Phb2mentioning
confidence: 99%